Alleviating drought stress in rice plant through intervention of Trichoderma spp. - Datta, D.; Senapati, A.K.; Behera, L.; Zaidi, N.W.; Kumar, S.; Dey, P. (Triveni Enterprises, 2023)
Aim: Trichoderma provides resistance to abiotic stress by generating a variety of secondary metabolites, phytohormones, through nutrient solubilization. The current study was conducted to determine whether Trichoderma could be used to alleviate drought stress in rice. Methodology: Three distinct isolates of Trichoderma harzianum [94 (A),T-14, IRRI-2] obtained from the International Rice Research Institute India, as well as two native isolates of Trichoderma asperellum (OT-3) and Trichoderma harzianum (0T-8) obtained from the farmlands of OUAT through serial dilution, were inoculated through seedling root dip treatment. Different morphological (days to active tillering, plant height, panicle initiation, root length, leaf rolling score, number of unfilled and filled grains per panicle) and biochemical data (Total phenolic content, malondialdehyde, proline, hydrogen peroxide, lignin and peroxidase) were estimated to determine the stress due to drought. Results: In-vivo studies on plant height, root length, number of filled grains, grains per panicle and leaf rolling that are positively associated with grain yield revealed that the application of Trichoderma had increased the grain yield. The effect of various biochemical characteristics, such as increase in phenol, peroxidase, lignin and cell membrane stability, which are known to alleviate drought stress through a variety of mechanisms were observed in this study. Inoculation of Trichoderma reduced the levels of oxidative chemicals such as proline, malondialdehyde, and hydrogen peroxide. Interpretation: The biochemical and morphological changes found in this study support the hypothesis that Trichoderma had a positive impact on yield and drought stress. Key words: Drought, Rice, Stress-related enzymes, Trichoderma spp